Laboratory findings of postoperative venous thromboembolism (VTE) in Dr. Sardjito General Hospital, Yogyakarta - Supomo; Mulyono, Budi; Sukorini, Usi; Arjana, Adika Zhulhi; Novenanto, Tandean Tommy (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Venous thromboembolism (VTE) is a significant risk, especially for older individuals. Indonesian studies found 37.1% VTE incidence in bedridden patients over 40 and 2.1% in major surgeries. Surgery, like hip fractures, raises the risk temporarily. Diagnosis relies on tests like ultrasound with Doppler, Wells score, and neutrophil-to-lymphocyte ratio (NLR). This study aimed to evaluate the laboratory findings of postoperative VTE. A retrospective analysis was conducted in Dr. Sardjito General Hospital, Yogyakarta using medical record data of VTE patients who underwent major surgery. The laboratory data, including complete blood count characteristics for every month for three months after postsurgery and DVT presentation when it occurred on the diagnostic day were collected. In total of 27 patients involved in this study, VTE cases were more common in digestive (41.2%) and obstetric gynecology surgeries (29.4%) for females, and nervous (44.4%) and cardiovascular surgeries (22.2%) for males. Females had a higher prevalence of Well Score ≥3 (82.4% vs 40%; p=0.058) and longer VTE therapy durations (65.50 ± 46.51 vs 39.60 ± 41.04 d; p=0.172). Males had more unilateral VTE occurrences (90.9 vs 56.3%; p=0.070) and a higher proportion of total occlusion cases (60 vs 37.5%; p=0.422). NLR exhibited a significant decrease from the 1st to the 2nd month (10.52 vs 3.64; p=0.009), followed by an insignificant increase in the 3rd month (3.64 vs 3.98; p=0.878). Notably, NLR trended downward in the 2nd month examination. In conclusion, VTE occurs in 0.21% of postoperative patients, with the highest incidence observed in post-gynecological surgery patients. The NLR can serve as a diagnostic tool for VTE in extremities, as an elevated NLR indicates the presence of a more proximal thrombus.